2018
DOI: 10.1177/1077559518796336
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Trauma-Informed Care Initiative in a State Child Welfare System: A Randomized Study

Abstract: Trauma-informed care (TIC) initiatives in state child welfare agencies are receiving more attention, but little empirical evidence exists as to their efficacy. The purpose of this study was to assess changes in self-reported practices and perceptions of child welfare staff involved in a multifaceted, statewide TIC intervention. Ten child welfare offices were matched and randomized to an early or delayed cohort. Staff were surveyed at Time 1 prior to any intervention, Time 2 postintervention for Cohort 1, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…While the above studies reported positive results of team training, a few reported null results (e.g., Raghav, 2018;Trojan et al, 2009). Beyond health care, studies in banking (Siddique et al, 2019) and pharmaceuticals (Koulikoff-Souviron & Harrison, 2010) found positive effects of team training on relational coordination, while a study of team training in the youth service sector found no effect (Jankowski et al, 2019).…”
Section: Selection and Training For Teamworkmentioning
confidence: 98%
“…While the above studies reported positive results of team training, a few reported null results (e.g., Raghav, 2018;Trojan et al, 2009). Beyond health care, studies in banking (Siddique et al, 2019) and pharmaceuticals (Koulikoff-Souviron & Harrison, 2010) found positive effects of team training on relational coordination, while a study of team training in the youth service sector found no effect (Jankowski et al, 2019).…”
Section: Selection and Training For Teamworkmentioning
confidence: 98%
“…110 In a multifaceted, statewide program spanning child welfare, mental health, and juvenile justice in New Hampshire, the Partners for Change Project implemented case planning for youth who had been screened for trauma, multisystem collaboration, and evidence-based trauma treatments across systems, resulting in improvements in case planning, trauma screening, mental health referrals, and overall system performance. 116 Because the child and family population in child welfare and juvenile justice system is known to have much higher healthcare needs, including physical, mental health and preventive care, implementing TIC in these systems could eventually have a significant impact on health care needs and outcomes of this vulnerable population. 79,99,104,117 Healthcare and educational systems also interact frequently.…”
Section: Statewide Efforts To Build Workforce Capacity and Integrate mentioning
confidence: 99%
“…21 However, there is currently a lack of evidence about the impact of whole-system trauma-informed approaches on outcomes for service-users, along with a lack of consistency when defining its components. 23 Exploration of these is likely to be an important element of clinical pathway development in this area, using learning from other areas – such as the offender personality disorder pathway - in which whole-system approaches have been introduced and evaluated. 24…”
Section: Interventions For Traumatic Stress In Prisonsmentioning
confidence: 99%